PENGARUH BIMBINGAN BELAJAR TERHADAP HASIL BELAJAR SISWA (Studi Kasus : Les Privat Dan Aplikasi Ruang Guru Di Sma Negeri 5 Pekanbaru) - Larissa Jusivani; Gimin Gimin; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the differences in learning outcomes between private tutoring and the application of the ruang guru. The population used in this study were all students of SMA Negeri 5 Pekanbaru. The sample in this study amounted to 35 students consisting of class X, XI, and XII at SMA Negeri 5 Pekanbaru. The data was obtained by using a google form which contains a questionnaire and the value of tutoring and the ruang guru application. The research data was taken using purposive sampling with the criteria of the research sample being students who had taken private lessons and had used the ruang guru application. The data analysis technique used in this research is the independent t test. The results of this study indicate that private lessons with a percentage of 47% and a ruang guru application with a percentage of 64.7% are categorized very well for student learning outcomes at SMA Negeri 5 Pekanbaru based on the results of variable categorization. From the learning outcomes obtained, data. From the simple linear regression hypothesis test obtained, the data shows a significance > 0.05, this means that private tutoring and the application of the ruang guru have no effect in improving learning outcomes. From the independent t test, the results of the F test show that the F value is 0.424 with sig. 0.519. Because the value of sig > 0.05, the variance of the two groups is homogeneous. Therefore, the t test used is the top t test (pooled t test). The results of the t test found the t value of -1.784 with a sig (2-tailed) of 0.084. Because the value of sig > 0.05, information is obtained that there is no difference in the results of the questionnaire between private lessons and ruang guru application. This means, students who have taken lessons and have used the teacher's room both assume that following both can improve learning outcomes. From the statistical table performed in hypothesis testing using the independent t test, it shows that the average score of students who have used the ruang guru application is more effective in improving learning outcomes with a difference of 3.06. Then it was obtained information that using the ruang guru application was more influential in improving student learning outcomes at SMA Negeri 5 Pekanbaru.Key Words : Private Tutoring, Ruang Guru Application, Learning Outcomes